A “experiência” no ensino de filosofia : possibilidades de uma educação humanizada no CASE-Cuiabá - Silva, Rogério Gonçalves e (2021)
The present work aims to point out the results of the Professional Masters in Philosophy research at UFMT, whose objective was to identify an adequate methodology for teaching Philosophy in the care of adolescents deprived of their liberty, which addresses content capable of providing a humanized teaching to these young people. who comply with socio-educational measures at the Socio-educational Service Center in Cuiabá. The texts used to be part of the philosophy classes were selected aiming to make reflections, dialogues and problematize the students' daily lives, where the use of clippings from television series for sensitization and notes was the main line of this research, being verified during the research that the readjustment of philosophy classes provided an opportunity for teaching, in which speaking and listening, writing and reading happened in a unique, active way, and that was not regulated by our knowledge, thus collaborating for the effective act of philosophizing. This proposal extols the relevance of “experience” in a Larrosian perspective, hoping thus to materialize the act of philosophizing, putting in common what we think, elaborating with the other the meaning or absence of meaning of what happens to us, seeking to explore students' experience, not only superficially, but emphasizing freedom of decision, allowing the student to consciously participate in the construction of knowledge, thus developing their critical sense. Due to the Covid-19 Pandemic, classes were suspended at the Socio-Educational Center and the research was not carried out in its entirety as planned. The transformation of the didactic unit of this dissertation into a didactic material to be used in the future in these environments of resocialization of adolescents, opens space for an original path in the construction of the understanding of reality, represents a very incisive contribution in the process of resocialization.